2016
DOI: 10.1111/2047-3095.12128
|View full text |Cite
|
Sign up to set email alerts
|

Dying Care Nursing Intervention in the Institutional Care of End‐of‐Life Patients

Abstract: Průřezová deskriptivní studie využívající strukturovaného dotazníku pro určení frekvence aktivit Péče o umírající prováděné 201 sestrou. VÝSLEDKY: Sestry u pacientů v závěru života častější využívají aktivity zaměřené na fyzický komfort. Významné vztahy byly nalezeny mezi frekvencí některých aktivit a úrovní vzdělání sester, délkou praxe a typem pracoviště. ZÁVĚRY: Sestry uváděly nepříliš časté používání komunikačních aktivit s pacienty a příbuznými, což souvisí s délkou jejich praxe. KLINICKÁ RELEVANCE: Je tř… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Similar results have been confirmed when assessing independence using the Modified Barthel Index [10] or when using the Instrumental Activities Daily Living Test [11]. The support of independence and physical comfort as a QoL dimension should rank among the most frequently administered nursing interventions [32, 33].…”
Section: Discussionmentioning
confidence: 60%
“…Similar results have been confirmed when assessing independence using the Modified Barthel Index [10] or when using the Instrumental Activities Daily Living Test [11]. The support of independence and physical comfort as a QoL dimension should rank among the most frequently administered nursing interventions [32, 33].…”
Section: Discussionmentioning
confidence: 60%
“…To deliver high-quality care, healthcare professionals must understand the principles of EOL care and be able to put them into practice. Competence in symptomatic treatment, such as fundamental care and pain management, is considered to be an essential part of EOL care (22,23). It has been observed that physical needs of the patients are usually prioritised, and emotional support and spiritual needs of the dying patient are rarely provided (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is concern in the scientific literature regarding nutritional management and the provision of nutritional support that is culturally acceptable, as evidenced in a study conducted in three Czech regions, which determined the frequency of the NIC in terminal patients 19 .…”
Section: Discussionmentioning
confidence: 99%